Anemia and outcomes following left ventricular assist device implantation. Issue 8 (4th March 2022) - Imamura, Teruhiko; Narang, Nikhil; Besser, Stephanie; Rodgers, Daniel; Combs, Pamela; Siddiqi, Umar; Stonebraker, Corinne; Jeevanandam, Valluvan
Abstract: Background: Patients with concomitant anemia and congestive heart failure have poor outcomes. The prevalence and clinical risk of anemia in patients receiving durable left ventricular assist devices (LVAD) remain unknown. Methods: We retrospectively analyzed patients who underwent LVAD implantation between 2014 and 2018. The association between hemoglobin level at the time of index discharge and the one‐year composite endpoint of heart failure readmissions or hemocompatibility‐related adverse events was investigated. Results: A total of 168 patients (57 [48, 66] years old, 123 males) were included and stratified into a classification of anemia (hemoglobin <9.7 g/dl, N = 99) or non‐anemia ( N = 69). The anemia group had a higher one‐year incidence of the composite endpoint (56% vs 36%, p = .013) with an adjusted hazard ratio of 1.83 (95% confidence interval 1.08–2.82). Patients with anemia also experienced suboptimal bi‐ventricular unloading. Conclusions: Anemia was prevalent in LVAD patients and associated with a greater risk of heart failure and hemocompatibility‐related adverse events. The optimal threshold for therapeutic intervention in response to post‐LVAD anemia needs further investigation. Abstract : Anemia was prevalent and associated with a greater risk of heart failure and hemocompatibility‐related adverse events in LVAD patients.